# |
ODE |
CAS classification |
Solved? |
\[
{}\left (x +y\right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}{y^{\prime }}^{3}+\left (x +y-2 x y\right ) {y^{\prime }}^{2}-2 y^{\prime } x y \left (x +y\right ) = 0
\] |
[_quadrature] |
✓ |
|
\[
{}\left (\sin \left (y\right )^{2}+x \cot \left (y\right )\right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}y^{\prime } \sqrt {X} = 0
\] |
[_quadrature] |
✓ |
|
\[
{}{y^{\prime }}^{2}-2 x^{2} y^{\prime }+2 y^{\prime } x = 0
\] |
[_quadrature] |
✓ |
|
\[
{}\left (x^{2}-a y\right ) {y^{\prime }}^{2}-2 x y y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}{y^{\prime }}^{3}+\left (2 x -y^{2}\right ) {y^{\prime }}^{2}-2 x y^{2} y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}{y^{\prime }}^{3} \left (2 y+x \right )+3 {y^{\prime }}^{2} \left (x +y\right )+\left (y+2 x \right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}y^{\prime } x = 0
\] |
[_quadrature] |
✓ |
|
\[
{}\frac {y^{\prime }}{x +y} = 0
\] |
[_quadrature] |
✓ |
|
\[
{}\frac {y^{\prime }}{x} = 0
\] |
[_quadrature] |
✓ |
|
\[
{}y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}c y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}a \sin \left (x \right ) y x y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}f \left (x \right ) \sin \left (x \right ) y x y^{\prime } \pi = 0
\] |
[_quadrature] |
✓ |
|
\[
{}y^{\prime } x = 0
\] |
[_quadrature] |
✓ |
|
\[
{}5 y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}{\mathrm e} y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}\pi y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}y^{\prime } \sin \left (x \right ) = 0
\] |
[_quadrature] |
✓ |
|
\[
{}f \left (x \right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}\left (x -1\right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}y y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}x y y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}x y \sin \left (x \right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}\pi y \sin \left (x \right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}x \sin \left (x \right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}2 y^{\prime } y^{\prime \prime \prime }-3 {y^{\prime }}^{2} = 0
\] |
[[_3rd_order, _missing_x]] |
✓ |
|
\[
{}{y^{\prime }}^{3}-y^{\prime } {\mathrm e}^{2 x} = 0
\] |
[_quadrature] |
✓ |
|
\[
{}\frac {y^{\prime }}{\frac {x}{y}-\sin \left (y\right )} = 0
\] |
[_quadrature] |
✓ |
|
\[
{}{y^{\prime }}^{3}+2 x {y^{\prime }}^{2}-y^{2} {y^{\prime }}^{2}-2 x y^{2} y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}{y^{\prime }}^{3} \left (2 y+x \right )+3 {y^{\prime }}^{2} \left (x +y\right )+\left (y+2 x \right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{3}+y \left (1+x^{2} y\right ) {y^{\prime }}^{2}+y^{2} y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}{y^{\prime }}^{3}+2 x {y^{\prime }}^{2}-y^{2} {y^{\prime }}^{2}-2 x y^{2} y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|
\[
{}{y^{\prime }}^{3} \left (2 y+x \right )+3 {y^{\prime }}^{2} \left (x +y\right )+\left (y+2 x \right ) y^{\prime } = 0
\] |
[_quadrature] |
✓ |
|